Behind The Mask: An Analysis of the Dedication of Shakespeare’s Sonnets and Its Implications for the Shakespeare Authorship Question - Sturrock, Peter; Erickson, Kathleen E (Journal of Scientific Exploration, 2020)
There is at present no consensus concerning the true authorship of the monumental literature that we ascribe to “Shakespeare”. Orthodox scholarship attributes this corpus to a man who was born and who died in Stratford-Upon-Avon, who spelled his name William Shakspere (or variants thereof, almost all with a short “a”), who could not write his own name consistently, and who may have been illiterate – as were his parents and as were, essentially, his children. For these and other reasons, many alternative candidates have been proposed. At this date, the leading such candidate is Edward de Vere, 17th Earl of Oxford. We approach the Authorship issue from a scientific perspective. We frame the key question as that of Secrecy or No Secrecy. According to orthodox scholarship, the Authorship Issue does not involve considerations of secrecy. According to independent scholarship, considerations of secrecy are fundamental to the Authorship Issue. We follow the initiatives of Jonathan Bond, John Rollett, and David Roper, who all brought their considerable mathematical expertise to the challenge of identifying and deciphering cryptograms embodied in the Dedication of the Sonnets and in the Inscription on the “Shakespeare” Monument. We show that the combined statistical significance of the cryptograms is overwhelming: The probability that the evidence contained in the cryptograms has occurred by chance rather than by intent is less than one part in one million-billion. Hence the messages must be accepted as the intentional creations of the authors – Oxford (not Thomas Thorpe, as usually assumed) for the Dedication, and Ben Jonson for the Inscription. The cryptograms confirm the orthodox suspicion that the intended recipient of the Sonnets was Henry Wriothesley, 3rd Earl of Southampton (so also confirming the orthodox belief that Southampton was the “Fair Youth” of the Sonnets). These discoveries resolve some of the well-known outstanding puzzles concerning the Authorship Issue such as the Author’s familiarity with Europe and its languages (especially Italy), his intricate knowledge of the lives of monarchs and nobility, his detailed and highly accurate knowledge of the law, etc. (see Table 1). However, this change in perspective necessarily raises new questions that will call for new research. Keywords: Shakespeare, Edward de Vere, William Shakspere, cryptograms, Cardano Grille